The digital ingredients of donation-based crowdfunding. A data-driven study of Leetchi projects and social campaigns. Issue 3 (3rd July 2018) - Sokolova, Karina; Perez, Charles
ABSTRACT: Crowdfunding platforms have seen increasing success over the last few years. While crowdfunding by counterparts has been extensively studied, only a very few works have focused on donation-based crowdfunding. The authors analyze Leetchi money-pots and study the impact of project presentations and Twitter campaigns on the success of fundraising. They propose a data-driven approach to determine the social strategies applied by the projects' owners and their relevance to the success of the crowdfunding process. The authors extracted and computed a set of quantitative indicators using data mining and graph analysis techniques, including the project page and Tweets content, Twitter promoters and message diffusion process. The authors evaluate the predictive power of 70 features on levels of success using a dataset of 1, 415 projects with 50, 119 project-related tweets. The paper provides recommendations concerning key indicators to be followed and potential strategies to apply when attempting to raise funds on donation platforms.